A rich weapon burial from the Late Roman Iron Age at Veldbæk, Denmark – : comments on the distribution of power in southern Jutland - Alexiou, Bente Grundvad; Grundvad, Lars; Jensen, Xenia Pauli (Danish Journal of Archaeology, 2022)
During two campaigns in 1997 and 1999, archaeologists from Esbjerg Museum excavated a spectacular Late Roman Iron Age weapon burial at Veldbæk in Esbjerg, Denmark. In addition to full weaponry, the deceased was buried with magnificent grave goods such as gilded fittings for a military belt, gaming pieces, a gold finger ring, a silver animal fibula, a red carnelian intaglio, and a copper-alloy-clad wooden bucket. The assemblage dates the grave to the transition between periods C1b and C2 of the Late Roman Iron Age, which is to say ca. AD 250 or shortly thereafter. The grave is a crucial new piece in the puzzle to understand how power was distributed in southern Jutland during the Late Roman Iron Age.